The combined effect of fire and nitrogen addition on biodiversity and herbaceous aboveground productivity in a coastal shrubland - Qi, Luyu; Song, Yixin; Zhang, Puyi; Sun, Wenlong; Wang, Wei; Yi, Shijie; Li, Jing; Liu, Haifang; Bi, Zhenggang; Du, Ning; Guo, Weihua (Frontiers in Plant Science, 2023)
Introduction Fire and nitrogen (N) deposition each impact biodiversity and ecosystem productivity. However, the effect of N deposition on ecosystem recovery after fire is still far from understood, especially in coastal wetlands. Methods We selected a typical coastal shrubland to simulate three N deposition levels (0, 10, and 20 g N m−2 year−1) under two different burned conditions (unburned and burned) in the Yellow River Delta of North China. Soil properties, soil microbial biodiversity, shrub growth parameters, herbaceous biodiversity, and aboveground productivity were determined after experimental treatments for 1 year. Results We found that fire had a stronger influence on the ecosystem than N addition. One year after the fire, shrub growth had significantly decreased, while soil pH, soil electrical conductivity, herbaceous biodiversity, soil microbial biodiversity, and herbaceous aboveground productivity significantly increased. Conversely, a single year of N addition only slightly increased herbaceous aboveground productivity. The combined effect of fire and N addition was only significant for fungus biodiversity and otherwise had minimal influence. Interestingly, we found that herbaceous aboveground productivity was positively associated with fungal community diversity under unburned conditions but not in burned shrublands. Fire showed a great impact on soil parameters and biodiversity in the coastal wetland ecosystem even after a full year of recovery. Discussion Fire may also diminish the influence of several belowground factors on herbaceous aboveground productivity, which ultimately reduces recovery and stability. Appropriate N addition may be an effective way to improve the ecosystem productivity in a wetland dominated by shrub species.